2018
DOI: 10.1161/atvbaha.117.310211
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR Gene and Serum Folate Interaction on Serum Homocysteine Lowering

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00794885.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…Therefore, in our study, we selected two GRS methods, SC-GRS and wGRS (DL-GRS), to analyse the efficacy on efficacy of folic acid treatment for HHcy. The direction of the six SNP affecting the efficacy of folic acid therapy was consistent with previous studies (17,18,(24)(25)(26)(27) . Especially, three SNP (rs1801131, rs1801133 and rs1801394) showed significant association with the folic acid efficacy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, in our study, we selected two GRS methods, SC-GRS and wGRS (DL-GRS), to analyse the efficacy on efficacy of folic acid treatment for HHcy. The direction of the six SNP affecting the efficacy of folic acid therapy was consistent with previous studies (17,18,(24)(25)(26)(27) . Especially, three SNP (rs1801131, rs1801133 and rs1801394) showed significant association with the folic acid efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…We selected six previously identified SNP affecting the efficacy of folic acid therapy (17,18,(24)(25)(26)(27) . All these SNP had minor allele frequency > 0•05 in the Chinese population.…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…In those who are homozygous for the mutation (TT genotype), enzyme function is only 30% of normal, and data provide evidence that nutrition can counteract genetic susceptibility. Recently, large, randomized trial in a population without mandatory FA fortification demonstrated that the adverse effect of the TT genotype on tHcy levels can be ameliorated by raising serum folate levels above the threshold (15 ng/mg or 34 nmol/L) via FA treatment and it provides new evidence to support a personalized FA treatment [94]. The gene-nutrient interaction between MTHFR C677T variant and folate status was also observed on the risk of anencephaly.…”
Section: Epigenetic Genetic and Nutrigenomic Risk Factors For Congementioning
confidence: 97%
“…Low folate status (as defined by various measures including blood folate concentrations, folate intake, and/or FA intake) has been associated with an increased risk of cardiovascular disease, cancers, CAs, CHD, and NTD [5,6,[89][90][91][92][93][94]. Also, this deficiency is clearly detrimental to the embryo and shows possible longer-term risks of diabetes or other health outcomes and health problems associated with child mortality and morbidity [95].…”
Section: Epigenetic Genetic and Nutrigenomic Risk Factors For Congementioning
confidence: 99%
See 1 more Smart Citation